Bovine superoxide dismutase and copper ions potentiate the bactericidal effect of autoxidizing cysteine. - Nyberg, G K (1979)
When cysteine is oxidized by oxygen, hydrogen peroxide is formed, and hydrogen peroxide is very toxic to Peptostreptococcus anaerobius VPI 4330-1. Native and inactivated superoxide dismutase increased the rate of oxidation of cysteine and thereby potentiated the toxic effect of cysteine. A similar increase in the rate of oxidation of cysteine and in the toxicity of cysteine was obtained with Cu2+.